Os cavaleiros da triste figura: uma experiência decolonial a partir de um processo artístico de criação cênica com o Grupo Teatral Boca de Cena de Aracaju-SE - Alves, Rogério Santos (2020)
This research objective to analyze the elements of popular culture when evidencing political and esthetic questions and rethink the presences and use of popular culture within the play “Os Cavaleiros da Triste Figura” (The Sad-Figured Knights), presented by the Sergipano theater group “Boca de Cena”, It was inspired in Miguel de Cervantes’ novel from Don Quixote de La Mancha from the concept of cultural hybridities and in a de colonial perspective. For that I shall retrace the steps of the play production in a study, to analyze and locate the use of popular culture concept in a postcolonial perspective trabalhada por Homi Bhabha, Néstor García Canclini (HIBRID CULTURE), Boaventura de Souza Santos (RESISTANCE FOCUS ), Stuart Hall (IDENTITY AND MODERNITY). . I will use records made by the theater group, as well as all empirical evidence developed during the play production, from the early stage of production until it reached the public, with experiences and statements reported by those involved in the cenic project looking forward to comprehend the presence and use of popular culture. To achieve these goals I will use as work methodology the exploratory research, making use of bibliographic and documental appointment connecting visual information and analysis of the group’s collection: pictures , interviews and videos of the early play production process, applying the “participant observation” method, as approached by Márcio Luiz Marietto (2011), and of “Escrevivência”, by Conceição Evaristo, without losing the trail of the “to speech place” concept, by Djamila Ribeiro, with the use of “content analysis”, in a Bardin approach as a way to locate and understand the presence and use of popular culture, in a perspective of cultural hybridism on the development and realization of the play.